Linda Mason y Roger Brown, Rice, Rivalry and Politics. Managing Cambodian Relief, Notre Dame, Indiana, University of Notre Dame Press, 1983, 218 pp. - Marisela Connelly (El Colegio de México, A.C., 1989)
-